ISOLATION AND CHARACTERIZATION OF PLANT GROWTH PROMOTING BACTERIA (PGPR) FROM RHIZOSPHERE OF OKRA - Touseef Bashir; Madiha Iqbal; Shahzeb Javed; Jaweria Riaz; Nain Taara Bukhari; Iqbal Nisa; Ghufran Ullah; Maleeha Nisar; Nimra Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Plant growth promoting bacteria (PGPR) are a type of bacteria that inhabit the rhizosphere of plants and can aid in the growth of plants, either directly or indirectly. Many different bacterial species have been studied for their ability to promote plant growth, including Pseudomonas, Azospirillum, Azotobacter, Klebsiella, Enterobacter, Alcaligenes, Arthrobacter, Burkholderia, Bacillus, and Rhizobium. The aim of the present study is to identify and isolate such bacteria from the rhizosphere of okra. The serial dilution approach was used in the current investigation to perform the isolation on LB-agar media. 15 strains were obtained for the characterization based on physical characteristics. Isolated isolates were identified using biochemical tests and morphological basis in vitro. 09 strains were gram positive while 05 strains were gram negative when stained it. In the current study, phosphate solublization was detected in seven bacterial isolates. Almost all of the bacterial isolates demonstrated IAA production. Twelve isolates tested positive for ammonia generation. All isolates were negative for HCN production. Fourteen isolates had nitrogen activity. Eleven isolates, nine isolates, and eleven isolates strains, respectively, demonstrated the activities of protease, pectinase, and amylase. To improve plant development, the potential of these PGPR isolates needs to be tested further.